פתור (z + 3) (2-z) (1-2z)> 0?

פתור (z + 3) (2-z) (1-2z)> 0?
Anonim

תשובה:

#z in (-3, 1/2) uu (2, oo) # #

הסבר:

תן # (z) = (z + 3) (2-z) (1-2z) = (z + 3) (2z-1) (z-2) #

לאחר מכן #f (z) = 0 # מתי #z = -3 #, #z = 1/2 # ו #z = 2 #

שלוש נקודות אלו חצו את הקו האמיתי לארבע פעמים:

# (- oo, -3) #, #(-3, 1/2)#, #(1/2,2)# ו # (2, oo) #

אם #z in (-oo, -3) # לאחר מכן

# (z + 3) <0 #, # (2z-1) <0 #, # (z-2) <0 # לכן #f (z) <0 #

אם #color (אדום) (z in (-3, 1/2)) # לאחר מכן

# (z + 3)> 0 #, # (2z-1) <0 #, # (z-2) <0 # לכן #color (אדום) (f (z)> 0) #

אם #z ב (1/2, 2) # # לאחר מכן

# (z + 3)> 0 #, # (2z-1)> 0 #, # (z-2) <0 # לכן #f (z) <0 #

אם #color (אדום) (z in (2, oo)) # לאחר מכן

# (z + 3)> 0 #, # (2z-1)> 0 #, # (z-2)> 0 # לכן #color (אדום) (f (z)> 0) #

אז הפתרון הוא #z in (-3, 1/2) uu (2, oo) # #

גרף {(x + 3) (2-x) (1-2x) -40, 40, -12.24, 27.76}